The effect of exposure to vivo contraceptive ads on viewers' buying interest (survey of followers of the instagram account @vivo_id) - Yodian, Vico; Salman, Salman (UNIVERSITAS KALBIS, 2023)
Advertising is a form of persuasive communication with the aim of attracting consumers' buying interest in the advertised product. This research aims to determine whether there is an influence of exposure to Vivo contraceptive advertising on followers' buying interest from the Instagram account @vivo_id. This study uses a positivistic paradigm with a quantitative approach. Data was collected using a questionnaire to 100 @vivo_id followers. Based on the results of statistical tests, there is a strong, positive and significant relationship between exposure to Vivo contraceptive advertising and buying interest of @vivo_id followers. Besides that, the results of the coefficient of determination show that exposure to advertising for Vivo contraceptives has an influence of 89.49% on purchasing interest, while the remaining 10.51% is influenced by other factors.